Patterns of axillary lymph node metastases and recurrent disease in grade 1 breast cancer in a New Zealand cohort: Does ethnicity matter?. Issue 6 (December 2015) - Meredith, Ineke; Seneviratne, Sanjeewa; Gerred, Susan; Ramsaroop, Reena; Harman, Richard
Abstract: Background: In New Zealand, Māori and Pacific women are more likely than New Zealand/European women to present at a younger age with larger tumours and metastatic disease. Survival rates are also differential by ethnicity. Many factors are believed to be responsible for this including differences in comorbidities, delays to presentation and delays in treatment. It is unclear whether these differences exist amongst women with grade 1 cancer in New Zealand. Therefore, we examined patterns of axillary nodal involvement, recurrent disease and mortality in grade 1 breast cancer in New Zealand women, and whether ethnicity was an important predictor for any of these outcomes. Method: Data was retrieved from the Auckland Breast Cancer Registry (ABCR) and the Waikato Breast Cancer Registry (WBCR) which are prospective, population-based databases. All women newly diagnosed with grade 1 primary invasive breast cancer between 1 June 2000 and 31 May 2013 were identified from the two registries. Results: There were 2857 grade 1 breast cancers diagnosed over this time period. Axillary lymph nodes were involved in 19.0% of women, and 5.1% developed recurrent disease (locoregional or distant). Pacific and Māori women were more likely than NZ European women to have larger tumours and lymphovascular invasion (LVI). Predictors for axillary node involvement were tumour size greater than 10 mm, LVI and non-screen detected cancers. Tumour size greater than 10 mm, lobular carcinoma and BCS without radiotherapy were predictive of recurrent and or metastatic disease. Ethnicity was not observed to be an independent predictor for axillary nodal involvement, recurrent and/or metastatic disease, or breast cancer specific mortality amongst New Zealand women with grade 1 breast cancer. Conclusion: Ethnicity was not a predictor of axillary node involvement, recurrent disease or mortality in grade 1 breast cancer in our population.